Análise exergo-econômica da microgeração com o uso de motores de combustão interna a biodiesel no acionamento do compressor do sistema por compressão de vapor - Silva, Gerson Barbosa da (2016)
This wort, its preset the theoretical and experimental study of a vapor compression system (SRCV), with cooling capacity of 26kW (7.5TR) developed at the Recogás at the Federal University of Paraíba. At first is analyzed the efficiency of the refrigeration system for vapor compression, where the circulation of refrigerant fluid is done by a hermetic compressor one piston that is driven by an electric motor, the second time, is analyzed circulation of refrigerant fluid system which is generated by a compressor opened, which is also triggered by the internal combustion engine. The two refrigeration systems working with fixed rotation compressor. Thermodynamic analyzes are performed and termoeconômicas of a plant expansion project a result of the CHP energy. Aimed to this research was to evaluate the performance of the system, working at different times with mineral diesel and biodiesel blends this with the proportions equivalent to B5 (95% mineral diesel and 5% biodiesel) B20 (80% mineral diesel and 20 % biodiesel), B40 (60% mineral diesel and 40% biodiesel), B60 (40% mineral diesel and 60% biodiesel) and) and B80 (20% mineral diesel and 80% biodiesel). Making use of computer platform fo Labview temperatures and pressures in real times and routines of computing platform Engineering Equation Solver - EES and Excel, to generate simulations of the refrigeration cycle, which has been validated with the experimental data.